Pengaruh Kualitas Pelayanan Serta Sistem Kritik dan Saran Digital Terhadap Kepuasan Pengunjung Funtech Plaza Jawa Timur Park 3, Kota Batu - Hasna Dhiyaul Haq; Rr. Tri Istining Wardani; Tri Ramadani Arjo (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The increasing competition in the tourism industry encourages destination managers to improve service quality and utilize technology as a medium to collect visitors' feedback to enhance customer satisfaction. Funtech Plaza Jawa Timur Park 3 has implemented a web-based Digital Complaint and Suggestion System through computer booths. This study aims to analyze the influence of Service Quality and the Digital Complaint and Suggestion System on Visitor Satisfaction.This study employed a quantitative approach by collecting data through questionnaires distributed to visitors of Funtech Plaza Jawa Timur Park 3 using a purposive sampling technique. Data were analyzed using a Likert scale measurement, followed by validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination, partialand simultaneous tests.The results indicate that both Service Quality and the Digital Complaint and Suggestion System have a positive and significant effect on Visitor Satisfaction, both partially and simultaneously. These variables explain a substantial proportion of visitor satisfaction, indicating that high-quality services and the effective use of digital feedback systems play an important role in improving the visitor experience.In conclusion, Service Quality and the Digital Complaint and Suggestion System are important factors in enhancing Visitor Satisfaction at Funtech Plaza Jawa Timur Park 3, Batu City. Therefore, management is encouraged to continuously improve service quality and optimize the digital feedback system as an effective evaluation tool.